Pengaruh Pemberian Circuit Training Terhadap Peningkatan Daya Tahan Otot Tungkai Bawah Pada Atlet Pencak Silat - Untoro, Sophya Fadila Nisa; Rahim, Anita Faradilla; Lubis, Zidni Imanurrohmah (NHM PRESS, 2023)
Currently, many pencak silat athletes have low leg muscle endurance, causing a high risk of injury which can affect the condition of the pencak silat athletes. The purpose of this study was to determine the effect of circuit training on increasing lower limb muscle endurance in pencak silat athletes. The research method used quasi-experimental with a one group pretest-posttest design with a total of 21 respondents. The research instrument used the Jump Squat Test. By providing circuit training interventions 3x a week in 4 weeks. The result of the analysis test using shapiro wilk obtained a P-value of 0,000 > 0,005, so H0 was rejected and H1 was accepted, which means that there is an effect of circuit training on increasing lower limb muscle endurance in pencak silat athletes at UKM PSHT University of Muhammadiyah Malang.